T-Bet Expression Mediated by the mTOR Pathway Influences CD4+ T Cell Count in Mice With Lethal Candida Sepsis - Bai, Guangxu; Wang, Hao; Han, Wen; Cui, Na (Frontiers in Microbiology, 2020)
The sustained high morbidity and mortality of Candida sepsis are mainly caused by compromise of host immunity. Clinically, it is often manifested as a significant decrease in CD4+ T cell count, although the mechanism is unclear. We established a lethal mice Candida sepsis model and used Murine Sepsis Score to group mice with different disease severity to establish the influence of T-bet expression on CD4+ T cell count in Candida sepsis. We found that CD4+ T cell count decreased in Candida-infected compared to uninfected mice, and the degree of decrease increased with aggravation of sepsis. Expression of T-bet similarly decreased with worsening of sepsis, but it was significantly enhanced in candidiasis in comparison of naïve state. To clarify its possible mechanism, we measured the activity of mammalian target of rapamycin (mTOR), which is a key regulator of T-bet expression. The mTOR pathway was activated after infection and its activity increased with progression of sepsis. We used mice with T-cell-specific knockout of mTOR or tuberous sclerosis complex (TSC)1 to further inhibit or strengthen the mTOR signaling pathway. We found that mTOR deletion mice had a higher CD4+ T cell count by regulating T-bet expression, and the result in TSC1 deletion mice was reversed. These results demonstrate that T-bet expression mediated by the mTOR pathway influences the CD4+ T cell count in mice with Candida sepsis.